Case Study on Early Age Shrinkage of Cement-based Composites (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of this paper was to study the behaviour of new high-performance fibre-reinforced cement composite materials (FRCC) that are reinforced with polyvinyl alcohol (PVA) fibres. The shrinkage deformations at early age, the compressive strength and modulus of elasticity of the new compositions had been determined. Test results shows that the addition of PVA fiber 1.10% and 0.55% by weight of the cement has negligible influence on concrete drying shrinkage, however, it is affect the concrete plastic and autogenous shrinkage. The results of the experiments permitted the prediction of long-term deformations of the concrete. Wider use of this material permit the construction of sustainable next generation structures with thin walls and large spans that cannot be built using the traditional concrete.